Letter (copy) : Relief for Spain - Citrine, Walter,1887-1983
011-0151-001 F.I.de Sol. 138 WMC/WJB/AC/384 International 3rd February, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, RELIEF FOR SPAIN I telephoned your office this afternoon, and asked them to convey to you the following reply to your letter of 2nd February. With regard to the Joint meeting in Brussels, I am sorry to say that I am unable to go, being too pressed with work here. Our Assistant Secretary is away ill, and I cannot leave the office or spare the time for travelling. If the meeting could have been called in London, I could possibly have taken part. With regard to the proposed Conference, I doubt whether we can get a more representative one than the last, which was held in December, and I am not clear as to what practical policy we can pursue. Jouhaux told us at the last meeting that the French Trade Union Movement were now urging a policy of 100 per cent. non-intervention. So far as Great Britain is concerned, I can see no chance, as I have repeatedly said, of our Government altering its policy, no matter what pressure is brought to bear upon it. At the same time, I can quite realise the eagerness of the Spanish comrades to gain the support of other countries. What I am worried about is: what can we, as an international movement, do to help them more than we are already doing? I think it is up to them to make practical proposals as to what we can do, and as to how it can be done. I am not against a Conference being called, only doubtful as to any practical result accruing from it. It would not seem to be likely to have any more value than as a sentimental gesture. As to the venue of the Conference, I would prefer London to Geneva. Of course it is understood that in the event of a Conference being convened, it would be limited to organisations attached to the I.F.T.U. and L.S.I. Yours faithfully, General Secretary. 292/946/11/151